Kajian Historis Pendaratan dan Jejak Tentara Jepang Selama Pendudukan Militer di Batubara - Maulana, Imran (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Pantai Sejarah in Batubara became a strategic route for the Japanese army to dominate the East Sumatra region during the Japanese occupation, amidst Dutch dominance. Physical evidence, such as bunkers and other defense structures, still exists, but non-physcal evidence in the form of oral history and folklore also holds important information. Unfortunately, the younger generation of Batubara is less aware of the historical value of this site. This study aims to explore the history of the Japanese occupation in Batubara and its impact on the local community. The research method used is a qualitative approach with historical methods, including heuristics, source verification, interpretation, and historiography. Primary sources include interviews with historical witnesses and photo archives, while secondary sources consist of related books and journal articles. The research results show the negative impact of Japanese policies and the loss of many historical traces due to the lack of attention to site preservation.